2007
DOI: 10.1124/mol.107.037044
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization and Molecular Determinants of the Activation of Transient Receptor Potential V2 Channel Orthologs by 2-Aminoethoxydiphenyl Borate

Abstract: Despite its expression in different cell types, transient receptor potential V2 (TRPV2) is still the most cryptic members of the TRPV channel family. 2-Aminoethoxydiphenyl borate (2APB) has been shown to be a common activator of TRPV1, TRPV2, and TRPV3, but 2APB-triggered TRPV2 activation remains to be thoroughly characterized. In this study, we have developed an assay based on cell lines stably expressing mouse TRPV2 channels and intracellular calcium measurements to perform a pharmacological profiling of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 29 publications
2
75
1
Order By: Relevance
“…Store-independent Activation of Orai3 by 2-APB-It has been reported that 2-APB can activate several TRP channels, including TRPV1, TRPV2, and TRPV3 (27)(28)(29)(30). Here we show that 2-APB can also activate Orai3 channels, confirming and extending a previous report (31).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Store-independent Activation of Orai3 by 2-APB-It has been reported that 2-APB can activate several TRP channels, including TRPV1, TRPV2, and TRPV3 (27)(28)(29)(30). Here we show that 2-APB can also activate Orai3 channels, confirming and extending a previous report (31).…”
Section: Discussionsupporting
confidence: 80%
“…2-Aminoethyl diphenylborinate (2-APB) is a membranepermeable modulator of many ion channels, including Ins(1,4,5)P 3 receptors (26) and TRPV1, TRPV2, and TRPV3 channels (27)(28)(29)(30). In native and overexpression systems, it can potentiate SOCE or CRAC current at low concentrations (Ͻ5 M) and inhibit both at higher concentrations (14,15,(31)(32)(33).…”
mentioning
confidence: 99%
“…The observed differences in the Ca 2 þ measurements between both truncated TRPV2 orthologues could be attributed to many different experimental variables. TRPV2 activation by 2-APB is known to be species dependent 37,38 ; therefore the response of rat TRPV2 to 2-APB may be inherently different from that of rabbit TRPV2. A parallel characterization of how 2-APB interacts with rat versus rabbit TRPV2 may provide insights into how 2-APB activates TRPV2 orthologues.…”
Section: Resultsmentioning
confidence: 99%
“…While SKF96365 has been used extensively as a tool to define the functional roles of TRPC channels in various cell and tissue types (Bengtson et al, 2004;Fowler et al, 2007), previous studies reported notable overlapping effects on numerous channels in various organs (Merritt et al, 1990;Hong and Chang, 1994;Schwarz et al, 1994;Juvin et al, 2007;Liu et al, 2007). A high concentration of SKF96365 (30 M) partly affected low voltageactivated T-type calcium channels in Purkinje cells (Singh et al, 2010).…”
Section: Discussionmentioning
confidence: 99%